8(u+4)-4(u+9)=8

Simple and best practice solution for 8(u+4)-4(u+9)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(u+4)-4(u+9)=8 equation:


Simplifying
8(u + 4) + -4(u + 9) = 8

Reorder the terms:
8(4 + u) + -4(u + 9) = 8
(4 * 8 + u * 8) + -4(u + 9) = 8
(32 + 8u) + -4(u + 9) = 8

Reorder the terms:
32 + 8u + -4(9 + u) = 8
32 + 8u + (9 * -4 + u * -4) = 8
32 + 8u + (-36 + -4u) = 8

Reorder the terms:
32 + -36 + 8u + -4u = 8

Combine like terms: 32 + -36 = -4
-4 + 8u + -4u = 8

Combine like terms: 8u + -4u = 4u
-4 + 4u = 8

Solving
-4 + 4u = 8

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 4u = 8 + 4

Combine like terms: -4 + 4 = 0
0 + 4u = 8 + 4
4u = 8 + 4

Combine like terms: 8 + 4 = 12
4u = 12

Divide each side by '4'.
u = 3

Simplifying
u = 3

See similar equations:

| 90=3(6x-6) | | 9m+7=5m+27 | | 5(f-1)=15 | | 6z=(0.5z-8) | | -96=2-7(2-4n) | | 4(2y+1)-7y=18 | | 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 | | 5p-2q=23 | | 3(4s+4)=7 | | 4/3x3.14x343= | | 6(2l+2)=132 | | -1+3(7+3x)=83 | | 7m-3+2m=13+m | | sinx=1.5 | | 13x+5y=179 | | 25=40+3x | | 6(21+2)=132 | | 144=6(5x+4) | | 15x+7y=193 | | 3(a-2)=60 | | -88=2x-5(-2x+8) | | -4(8x-8)=192 | | (q-4)*7=-24 | | 3(x+1)+7=6(x+1)+63 | | 6+29=27+6+2 | | -92=7+3(4r-5) |

Equations solver categories